Change in health knowledge of Bangladeshi children: five years experience - Nath, Samir Ranjan; Chowdhury, A Mushtaque R. (BRAC Research and Evaluation Division (RED), 2020)
This article explores the improvement in the level of health knowledge of Bangladeshi children over a five year period 1993-1998. Data were generated from two nationally representative sample surveys covering respectively 2,520 and 3,360 children aged 11-12 years. Six health knowledge items, relevant to life in Bangladesh, were considered. Analyses revealed a significant improvement in the knowledge over the period. However, significant socio-economic variations also persisted in the performance. Rural children improved much faster compared to their urban counterparts. In both the surveys, children's performance varied significantly by items. To equip children with necessary health knowledge this study suggested strengthening health education at primary level in Bangladesh.